A systematic review of treatment for impulsivity and compulsivity - Aguilar-Yamuza, Beatriz; Trenados, Yolanda; Herruzo, Carlos; Pino, María José; Herruzo, Javier (Frontiers in Psychiatry, 2024)
The aim of this study was to comprehensively review existing treatments for impulsivity and compulsivity in non-substance addictions, driven by the importance of these factors in addictive disorder development and treatment efficacy. A systematic review carried out following PRISMA guidelines identified 14 articles from a total of 764 studies, highlighting the limited literature that is available on psychological treatments for non-substance addictions, in particular studies focusing on impulsivity and compulsivity. The studies were categorized by behavioral addiction type. For compulsive sexual behavior and problematic pornography use, cognitive-behavioral therapy (CBT) has shown significant improvements in compulsivity. In gambling disorder, interventions like cognitive bias modification and motivational interviewing combined with CBT have been effective in reducing impulsivity. Cognitive-behavioral therapy was advocated for compulsive shopping, although results varied. For problematic internet use, dialectical behavior therapy and acceptance and commitment therapy have been effective in addressing impulsivity. Despite literature supporting CBT for most behavioral addictions, the review noted that some articles indicate that dialectical behavior therapy and acceptance and commitment therapy were also effective for problematic internet use, suggesting different underlying mechanisms for this type of addiction. It also highlighted limitations, including the small number of studies and the lack of standardized assessment measures. Further research is needed to understand underlying mechanisms and develop tailored treatments for impulsivity and compulsivity in non-substance addictions. These findings offer new directions for research and intervention guidelines in behavioral addictions.